Intraoperative epidural analgesia practices and their outcomes in major abdominal surgeries at a tertiary care hospital - Gulamani, Amber; Rehman, Azhar; Nazir, Mohsin; Shabbir, Zainab (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the association involving site, concentrations and dosing of local anaesthetics used intraoperatively on postoperative pain scores, motor block and need for rescue analgesia. Method: The observational study was conducted June 1, 2020, to May 31, 2021, at the Aga Khan University Hospital, Karachi, and comprised patients planned for major abdominal surgeries with epidurals as primary analgesic modality. They were followed prospectively from placement of epidurals to 24h postoperatively. Data was collected from anaesthesia chart and pain management notes. Data was analysed using SPSS 19. Results: Of the 170 patients, 96(56.4%) were females and 74(43.5%) were males. The overall mean age was 54.1±12.6 years and mean body mass index was 26.7±5.5Kg/m2. More than half of the patients 110(64.7%) had thoracic epidural, while 60(35.3%) had lumber epidural. Requirement of opioid co-analgesia intraoperatively was significantly high with higher compared to lower concentration of local anaesthetics (p=0.004). The difference in frequencies of motor block was significantly associated with catheter length (p=0.006). Conclusions: Intraoperative management of epidurals is an essential but overlooked component of perioperative pain management. Guidelines should be formulated for intraoperative epidural analgesic regimens to improve postoperative outcomes. Key Words: Epidural management, Pain management, Local anaesthetics, Intraoperative period, Thoracic epidural, Practice trends.